Reasons and Countermeasures for the Runaway Fault of the Large Flat-headed Tower Crane Rotation - Wang Jidong; Xu Chunxiang; Dai Ronghua (Jixie chuandong)
With the two kinds of analysis methods of classification analysis and theoretical mechanical analysis,the runaway fault of the large flat-headed tower crane rotation is systematically analyzed,the possible reasons that could cause the tower crane rotation out of control are explained in detail,and the countermeasures of avoiding runaway fault and guaranteeing the tower crane safety are provided for its design,manufacture and its users.